SIMULATION OF DISTANCE BETWEEN FIELD AND REPLENISHMENT PUMP IN MECHANIZED SPRAYING OF SUGARCANE (Saccharum spp.) - Santos,Neisvaldo B. dos (2018)
ABSTRACT Brazil is the world's largest producer of sugarcane destined for mills. Spraying in sugarcane plantations is carried out in extensive cultivation areas and with self-propelled, tractor-driven, and aerial hydraulic equipment. For this, a good positioning of the replenishment pump of agricultural defensives close to the field where the spraying is carried out is necessary. However, it is desirable that the replenishment be carried out at short distances between the field and replenishment pump. This study aimed to assess the impact of the distance between the field and replenishment pump on the operational cost of hydraulic sprayers for sugarcane farming practices. Due to the difficulty in accomplishing the work and meeting the objective under field conditions, we decided to develop a computational model called “TratoCana” in a spreadsheet and programming language. The model was verified for possible routine errors, validated, and used in the analysis of factors and in the generation of scenarios. The results showed that the increased average distance between the field and replenishment pump has a negative impact on the operational and economic performance of the machine.